Environmentally conscious design of ethanol fed fuel cell system (2006)
In this work, a clean technology for electricity production from renewable sources is proposed. For this aim, an integration of bioethanol steam reforming and a fuel cell system (SOFC) was developed by computer aided design using HYSYS®. For process integration, was taking into account that steam reforming of bioethanol is an endothermic process and this reaction improves its conversion with fed steam excess. Moreover, typical SOFC operational conditions were used. An integrated flowsheet was developed using heat and mass integration of several process streams achieving high energy efficiency. Additionally, a discussion about other integration schemes is presented.